1. It is important to go through each of the words given in the question to get through to the actual answer. The function will be:
y= (4 * x) - 5
= 4x - 5
2. The function of this statement will be
(h/3) + 2.5 = w
1. Let us assume the price of a pizza = p
From the first part we can write
p = $6.95
On adding the price of each topping "t" we get
p = $6.95 + ($0.95) * t
= <span>$6.95 + $0.95t</span>
I hope it helps you.
Answer:
![f^{-1}(x) = \frac{1}{2}(x +4)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%20%3D%20%5Cfrac%7B1%7D%7B2%7D%28x%20%2B4%29)
Step-by-step explanation:
Given
![f(x) = 2x - 4](https://tex.z-dn.net/?f=f%28x%29%20%3D%202x%20-%204)
Required
Determine the inverse function
Start by replacing f(x) with y
![y = 2x - 4](https://tex.z-dn.net/?f=y%20%3D%202x%20-%204)
Swap the positions of y and x
![x = 2y - 4](https://tex.z-dn.net/?f=x%20%3D%202y%20-%204)
Make y the subject: <em>Add 4 to both sides</em>
![x+4 = 2y - 4+4](https://tex.z-dn.net/?f=x%2B4%20%3D%202y%20-%204%2B4)
![x+4 = 2y](https://tex.z-dn.net/?f=x%2B4%20%3D%202y)
Make y the subject: <em>Divide through by 2</em>
<em></em>
<em></em>
<em></em>
<em></em>
<em></em>
Replace y with f-1(x)
![f^{-1}(x) = \frac{1}{2}(x +4)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%20%3D%20%5Cfrac%7B1%7D%7B2%7D%28x%20%2B4%29)
The simplified expression of
is ![x^2+xy+y^2](https://tex.z-dn.net/?f=x%5E2%2Bxy%2By%5E2)
<h3>Complete question</h3>
Simplify the expression: (x³ + (-y)³) / (x - y)
Do not include parentheses in your answer.
<h3>How to simplify the expression?</h3>
The expression is given as:
![\frac{x^3 + (-y)^3}{(x - y}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E3%20%2B%20%28-y%29%5E3%7D%7B%28x%20-%20y%7D)
Open the inner bracket
![\frac{x^3 -y^3}{(x - y}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E3%20-y%5E3%7D%7B%28x%20-%20y%7D)
Apply the difference of two cubes to the numerator
![\frac{(x-y)(x^2+xy+y^2)}{(x - y}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-y%29%28x%5E2%2Bxy%2By%5E2%29%7D%7B%28x%20-%20y%7D)
Cancel out the common factors
![x^2+xy+y^2](https://tex.z-dn.net/?f=x%5E2%2Bxy%2By%5E2)
Hence, the simplified expression of
is ![x^2+xy+y^2](https://tex.z-dn.net/?f=x%5E2%2Bxy%2By%5E2)
Read more about expressions at:
brainly.com/question/723406
#SPJ1
For example, for LCM (12,30) we find:
Using the set of prime numbers from each set with the highest exponent value we take 22 * 31 * 51 = 60. Therefore LCM (12,30) = 60.
Answer:
(-3, 3).
Step-by-step explanation:
4x^2-36= 0
4x^2 = 36 Taking square roots of both sides:
2x = +/- 6
x = +/- 3.